Brasilianische Höhenflüge Luftfahrtpioniere und Imaginationen von Nation und Welt in Brasilien, 1900-1922 - Russ, Carla (Historamericana, 2022)
At a time when flying was more of a sensation than a matter of course, this technology fascinated people around the world. The book sheds light on the contemporary meaning of aviation in Brazil as well as Brazilian perspectives on a world that is increasingly growing together and one's own positioning in it.